2008
DOI: 10.4238/vol7-3gmr428
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of the kappa-casein gene in Brazilian cattle

Abstract: ABSTRACT. Frequencies of κ-casein gene alleles were determined in 1316 animals from the Brazilian Bos indicus genetic groups (Sindhi cows, Gyr sires, Gyr cows, Guzerat sires, Guzerat cows, Nellore sires, and Gyr x Holstein crossbreds) by means of polymerase chain reaction-restriction fragment length polymorphism analysis using two independent restriction nucleases (Hinf I and HaeIII). The genotyping of κ-casein alleles (A and B) is of practical importance, since the B allele is found to correlate with commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 22 publications
2
45
0
6
Order By: Relevance
“…K-Ca 'B' allele was reported to have a favorable and significant effect on both milk yield and milk protein content in Reggiana dairy local cattle , different Indian buffaloes breeds (Raj et al, 2008), nili-ravi buffalo (Riaz et al, 2008). Also, its favorable effect on milk technological properties and cheese yield in taurine and zebu cattle breeds (Ceriotti et al, 2004) and Brazilian cattle (Azevedo et al, 2008), desirable coagulation properties reported in Finnish Ayrshire cows (Ikonen et al, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…K-Ca 'B' allele was reported to have a favorable and significant effect on both milk yield and milk protein content in Reggiana dairy local cattle , different Indian buffaloes breeds (Raj et al, 2008), nili-ravi buffalo (Riaz et al, 2008). Also, its favorable effect on milk technological properties and cheese yield in taurine and zebu cattle breeds (Ceriotti et al, 2004) and Brazilian cattle (Azevedo et al, 2008), desirable coagulation properties reported in Finnish Ayrshire cows (Ikonen et al, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…The PCR-RFLP technique has been used to study the frequency of the κ-Cn genotypes (alleles) in bovines as well as for dairy ca le (Alipanah et al, 2005;Azevedo et al, 2008). Identifi cation of the variant genotypes of the κ-Cn gene in this study was also performed through the PCR-RFLP method.…”
Section: Amplifi Cationmentioning
confidence: 99%
“…The overall length of the κ-Cn gene is close to 13 kb, in the chromosome 6q31. The κ-Cn is considerably diff erent from other caseins in structure and other properties (Azevedo et al, 2008). The genetic polymorphism of the κ-Cn gene in ruminant has been well documented providing ca le (Pinders et al, 1991;Rij njkels et al, 1997), buff aloes (Pipalia et al, 2001;Otaviano et al, 2005;Patel et al, 2007;Riaz et al, 2008), goats (Angiolillo et al, 2002;Yahyaoui et al, 2003;Prinzenberg et al, 2005;Kiplagat et al, 2010), sheep (Moioli et al, 2007) and yak (Prinzenberg et al, 2008).…”
Section: Kappa-casein Genotypic Frequencies Inmentioning
confidence: 99%
“…These animals had already been genotyped for κ-casein polymorphism by PCR-RFLP with the restriction enzyme HinfI (Azevedo et al, 2008;Peixoto et al, 2012).…”
Section: Samplesmentioning
confidence: 99%
“…The κ-casein allele A has been associated with lower milk fat and calcium amount and a lower milk pH (Kürbarsepp et al, 2005). However, allele B is rare in indicine breeds selected for milk production and has not been found in meat selection zebu herds (Kemenes et al, 1999;Azevedo et al, 2008). To date, no report on the effects of this polymorphism on milk coagulation properties in cheese production in indicine breeds have been published.…”
Section: Introductionmentioning
confidence: 99%